Pengaruh Media Gambar untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PKN di Kelas V SD: The Influence of Image Media to Improve Student Learning Outcomes in Civics Subjects in Grade V of Elementary School - Nurmala Sari Harahap; Lurtian Sirait; Jubelando O. Tambunan (ITScience (Information Technology and Science), 2024)
The educational process is a journey of seeking knowledge that never stops throughout human life and is a very significant thing in human life. Real attention must be given to the quality of education in Indonesia to achieve the desired educational goals. Various initiatives have been carried out to improve the quality of national education, such as using media in civics learning. This type of research is quantitative, using an experimental method with a pre-experimental design in the form of a One Group pretest-posttest. The population in this study were all fifth-grade students of UPTD SDN, totaling 33, and the sample in this study was the entire population, namely fifth-grade students, totaling 33 students. The sampling technique used was total sampling with two research variables: independent variable (x), image media, and independent variable (y), student learning outcomes. The data collection technique was by test and took place in the 2024/2025 academic year. The analysis techniques used for this study were Normality, homogeneity, and t-test. In the normality test, the pretest value was 45.91, while the post-test value was 79.87. In the homogeneity test, the significant value is 143, which means it is greater than the significant value of 0.05, which means the data is homogeneous. Furthermore, in the t-test, based on the calculation results, the t_count value is obtained = 58.31 with a significant level of 0.00. So that t_count> t_table= 58.31> 2.03. Media influences student learning outcomes in civics learning in class V UPTD SDN 125549 Pematangsiantar.